High TRGV 9 Subfamily Expression Marks an Improved Overall Survival in Patients With Acute Myeloid Leukemia - Kong, Xueting; Zheng, Jiamian; Liu, Xiaxin; Wang, Wandi; Jiang, Xuan; Chen, Jie; Lai, Jing; Jin, Zhenyi; Wu, Xiuli (Frontiers in Immunology, 2022)
Background: The heterogeneous T cells in acute myeloid leukemia (AML) have the combinatorial variety generated by the different T cell receptor (TCR). γδ T cells are a distinct subgroup of T cells containing TCRγ (TRGV) and TCRδ (TRDV) subfamilies with diverse structural and functional heterogeneity. Our previous study showed clonally expanded TRDV T cells might benefit the immune response directed against AML. However, the feature of TRGV repertoire in AML remain unknown. To fully characterize the feature of γδ T cells, we analyzed the distribution and clonality of TRGV subfamilies (TRGV I-III), the proportions of γδ T cell subsets, and their effects on the overall survival (OS) of patients with AML. Methods: In this study, the complementarity-determining regions 3 (CDR3) size of TRGV subfamilies in γδ T cells of peripheral blood from de novo AML patients were analyzed, using Real Time PCR and Genescan techniques. Quantitative analysis of TRGV I-III subfamilies was performed by Real Time Quantitative PCR. The proportions of total γδ T cells and their subset were detected by multicolor flow cytometry assay. We further compared the correlation between the TRGV gene expression levels, the proportion of TRGV II+ TRDV2+ T cells, and OS in AML. Results: The expression frequencies and gene expression levels of three TRGV subfamilies in AML samples were significantly lower than healthy individuals (HIs). Moreover, compared with HIs, the proportions of total γδ T cells and TRGV II+ TRDV2+ T cells were significantly decreased in AML patients. In addition, AML patients who had the higher expression level of TRGV gene and the higher proportion of TRGV II+ TRDV2+ T cells showed the better OS. Furthermore, high expression levels of TRGV II and proportion of TRGV II+ TRDV2+ T cells were identified as independent protective factor for complete remission (CR) in AML patients. Conclusions: The restrictive of TRGV usage might relate to the preference of usage of γδ T cells. Higher expression level of TRGV subfamilies might be associated with the better OS in AML. Higher TRGV II expression and increased TRGV II+ TRDV2+ subfamilies might be prospected a better prognosis in AML patients.